Retrospective study of surgical cases of ruminants at Veterinary Teaching Hospital, Bangladesh Agricultural University - Al Noman, Zakaria; Hasan, Imam; Arif, M.; Ferdous, Jannatul; Sachi, Sabbya; Alam, Md. Rafiqul; Sikder, Mahmudul Hasan (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: A retrospective survey was designed to determine the prevalence and factors involved in surgical cases at the Veterinary Teaching Hospital (VTH), Bangladesh Agricultural University from June 2014 to June 2017. Materials and materials: In total, 1042 surgical cases of food animal (large ruminants: n=564, and small ruminants: n=493) and 26 non-food animal (mono-gastric animal) were recorded from patient register book and case recording card. Data were analyzed by Epi Info TM software and frequencies were calculated for different variables using Statistical Package for Social Science (SPSS) software. Result: In large ruminant, hernia (16.13%) ranked top (90% umbilical and 10% lateral) followed by fracture (14.89%), abscess (14.54%), umbilical myasis (10.46%), atresia ani (5.85%) and naval ill (4.07%). Among the reported cattle, 87.41% were crossbred and 12.59% were indigenous. Calf, heifer and adult cattle were 55.32, 10.29 and 34.39% respectively. In small ruminants, castration (32.94%; n=138) ranked top followed by myasis (10.55%) naval ill (10.31%), abscess (7.44%), dystocia (6.24%) and urolithiasis (5.49%). Based on surgical classification in large and small ruminants, 37.56 and 42.50% were reported for general surgery, whereas 28.71 and 7.15% for congenital, 11.18 and 13.12% for gynecological and 2.65 and 37.23 % for andrological problems, respectively. Male and female ratio was 1:1.31 and 2:1 respectively in large and small ruminants, respectively. Conclusion: This study emphasizes the factors related to successful surgical cases management at VTH. The results may help in controlling surgical related cases in Mymensingh region of Bangladesh. http://doi.org/10.5455/javar.2018.e252